Optical Fiber Communication Conference (OFC) 2023 2023
DOI: 10.1364/ofc.2023.tu3h.4
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Quantum Channel Monitoring via Quantum Wrappers

Abstract: We experimentally demonstrate quantum channel monitoring by wavelength-time multiplexing of classical wrapper bits with quantum payloads. Bit-error-rate measurements of 5 Gb/s classical bits infer the coincidence-to-accidental ratio of the quantum channel up to 13.3 dB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…We performed preliminary point-to-point QW datagram transmission experiments to gain insight into the feasibility of QW networking [15]. Further, we extended the testbed to a three-node network with a single source node connected to two distinct destination nodes via a QWSR node.…”
Section: Quantum Repeatersmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed preliminary point-to-point QW datagram transmission experiments to gain insight into the feasibility of QW networking [15]. Further, we extended the testbed to a three-node network with a single source node connected to two distinct destination nodes via a QWSR node.…”
Section: Quantum Repeatersmentioning
confidence: 99%
“…We observed that the CAR of the quantum channel degrades significantly to 2, if we utilize continuous headers due to the limited channel isolation of the demultiplexing WDM device. However, by time-division multiplexing the burst-mode headers and packetized quantum payloads, the CAR recovers to 18 [15]. Further, with a three-node experiment, we also performed a relatively long-distance transmission of 20 km, for two distinct destinations.…”
Section: Quantum Repeatersmentioning
confidence: 99%